Population connectivity of an overexploited coastal fish, Argyrosomus coronus (Sciaenidae), in an ocean-warming hotspot. Issue 1 (2nd January 2018) - Henriques, R; Potts, WM; Santos, CV; Sauer, WHH; Shaw, PW
Abstract : The West Coast dusky kob Argyrosomus coronus is a commercially exploited fish with a distribution confined to the Angola–Benguela Frontal Zone (ABFZ) of the southeastern Atlantic Ocean. A previous study revealed that during a recent period of local warming the species extended its distribution into Namibian waters, where it hybridised with the resident and congeneric Argyrosomus inodorus . Environmental changes are a major threat to marine biodiversity and when combined with overfishing have the potential to accelerate the decline of species. However, little is known regarding the evolutionary history and population structure of A. coronus across the ABFZ. We investigated genetic diversity, population structure and historical demographic changes using mtDNA control region sequences and genotypes at six nuclear microsatellite loci, from 180 individuals. A single, genetically homogeneous population was indicated across the distributional range of A. coronus (φST = 0.041, F ST = 0.000, D = 0.000; p > 0.05). These findings imply that the oceanographic features within the ABFZ do not appear to significantly influence population connectivity in A. coronus, which simplifies management of the species. However, reconstruction of the demographic history points to a close link between the evolutionary history of A. coronus and the environmental characteristics of the ABFZ. This outcome suggests the species' vulnerability to the rapid environmental changes being observed across this region, and highlights a pressing need for transboundary management to mitigate the impacts of climate change in this global hotspot of seawater temperature changes.